1996
DOI: 10.1161/01.cir.94.7.1506
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bcl-2 Protein, an Inhibitor of Apoptosis, and Bax, an Accelerator of Apoptosis, in Ventricular Myocytes of Human Hearts With Myocardial Infarction

Abstract: bcl-2 protein is induced in salvaged myocytes at the acute stage of infarction, but Bax protein is overexpressed at the old stage. The expression of bcl-2 and the overexpression of Bax may play an important pathophysiological role in the protection or acceleration of the apoptosis of human myocytes after ischemia and/or reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
212
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(232 citation statements)
references
References 24 publications
16
212
0
4
Order By: Relevance
“…SDF-1 increases Bcl-2/Bax ratio through the SDF-1/CXCR4 axis The Bcl-2 family proteins, including the pro-survival Bcl-2 and pro-apoptotic Bax, are key regulators of apoptosis (Misao et al, 1996;Li et al, 2007). To determine whether SDF-1 pretreatment modify the expression of Bcl-2 and Bax, MSCs were pretreated with SDF-1 for 1 h and then exposed to H 2 O 2 followed by re-oxygenation for 16 h. Western blotting showed that Bcl-2 level was increased in SDF-1 pretreated cells, but was significantly lower in AMD3100-treated cells (Fig.…”
Section: Sdf-1 Activates the Akt And Erk Pathways Through The Sdf-1/cmentioning
confidence: 99%
“…SDF-1 increases Bcl-2/Bax ratio through the SDF-1/CXCR4 axis The Bcl-2 family proteins, including the pro-survival Bcl-2 and pro-apoptotic Bax, are key regulators of apoptosis (Misao et al, 1996;Li et al, 2007). To determine whether SDF-1 pretreatment modify the expression of Bcl-2 and Bax, MSCs were pretreated with SDF-1 for 1 h and then exposed to H 2 O 2 followed by re-oxygenation for 16 h. Western blotting showed that Bcl-2 level was increased in SDF-1 pretreated cells, but was significantly lower in AMD3100-treated cells (Fig.…”
Section: Sdf-1 Activates the Akt And Erk Pathways Through The Sdf-1/cmentioning
confidence: 99%
“…Bcl-2 inhibits cell death by blocking cytochrome C release from the mitochondria [67], that otherwise leads to caspase activation and cell death. Bcl-2 is up-regulated in surviving ventricular myocytes in the context of MI [68], and transgenic over-expression of Bcl-2 in the engrafted cells limits myocardial infarct size after ischemia/reperfusion [69]. Li and colleagues have demonstrated the pro-survival effects of transduced Bcl-2 in two cell types: smooth muscle cells [69] and mesenchymal stem cells [70].…”
Section: Strategies To Increase Cell Survivalmentioning
confidence: 99%
“…Bifunctional apoptosis regulator (BAR) is an endoplasmic reticulum protein that inhibits cardiomyocyte apoptosis through interacting with the intrinsic apoptosis pathway (Chua et al, 2009). Bcl-2 protects cardiomyocyte from apoptosis (Misao et al, 1996;Imahashi et al, 2004). And cardiac specific Bcl-2 transgenic mice exhibit reduced infarct size and cardiomyocyte apoptosis (Brocheriou et al, 2000;Chen et al, 2001).…”
Section: Mitochondria Mediate Apoptosis In Heartmentioning
confidence: 99%